Synthesis And Characterization Of MgO And MgO/ZnO Multilayer Thin Films For Heat Spreading Application In Light Emitting Diode Packaging - Sani, Idris Muhammad (2021)
This research was carried out to synthesize magnesium oxide (MgO) and magnesium oxide - zinc oxide (MgO/ZnO) multilayer thin film as a TIM cum heat spreader for efficient thermal management in LEDs packaging system. MgO (10 layers) and MgO/ZnO multilayer (stacked separately in a configuration of 9:1, 8:2, 7:3, 6:4 and 5:5 layers) thin films are coated over aluminum (Al 5052 grade) and copper (Cu) substrates using spin coating technique. In the first part, MgO thin film was synthesis using 0.6 M, 10 coating cycles, preheated at 200 °C for 20 minutes, and finally annealed at 600 °C for 1 hour. Structural characterization by XRD shows the presence of (200), (220), and (222) MgO phases with crystalline size (37.47 nm), reduced microstrain (2.5 x 10-3) and dislocation density (7.0 x 10-4 lines/m2) for 0.6 M MgO coated Al. Uniform distribution of 74 nm size grains and surface roughness of 19.11 nm were confirmed by FESEM and AFM analysis. A significant difference in junction temperature (ΔTJ = 24.7%) and total thermal resistance (ΔRth-tot = 3.86 K/W) were recorded for LED fixed on 0.6 M MgO coated Al compared to that of bare Al. In the second part, ZnO was added to the monolithic MgO to improve the structural, surface, and thermal transport properties of MgO. Among the studied MgO/ZnO multilayers, 6:4 L MgO/ZnO displayed larger crystalline sizes of 52 nm (Al) and 35 nm (Cu) with thermal conductivity of 24.31 W/mK (Al), and 15.13 W/mK (Cu) respectively. 6:4 L MgO/ZnO multilayer films showed lower surface roughness (9.6 nm (Al) and 2.6 nm (Cu)) with uniformly distributed grains and presence of large numbers of contact points to the LEDs package